2020
DOI: 10.3389/fvets.2020.00624
|View full text |Cite
|
Sign up to set email alerts
|

TeamMate: A Longitudinal Study of New Zealand Working Farm Dogs. II. Occurrence of Musculoskeletal Abnormalities

Abstract: Musculoskeletal injury and disease are common in dogs, and a major cause of retirement in working dogs. Many livestock farmers rely on dogs for the effective running of their farms. However, the incidence of musculoskeletal disease has not been explored in working farm dogs. Here we explore the occurrence of musculoskeletal abnormalities in 323 working farm dogs that were enrolled in TeamMate, a longitudinal study of working farm dogs in New Zealand. All dogs were free of musculoskeletal abnormalities on enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…However, that study included also nonagility-related injuries and orthopedic conditions, likely leading to the higher proportions than in other studies [8]. The incidence of sport-or work-related injuries appears lower in agility dogs than in greyhounds, working farm dogs, or gundogs [13][14][15]. In flyball dogs, injury risk appears to be similar to agility dogs [11,16].…”
Section: Injury Ratementioning
confidence: 97%
“…However, that study included also nonagility-related injuries and orthopedic conditions, likely leading to the higher proportions than in other studies [8]. The incidence of sport-or work-related injuries appears lower in agility dogs than in greyhounds, working farm dogs, or gundogs [13][14][15]. In flyball dogs, injury risk appears to be similar to agility dogs [11,16].…”
Section: Injury Ratementioning
confidence: 97%
“…The prevalence of musculoskeletal injuries in our study (15.9%) closely matched results from Schuh-Renner et al (14.0%) 11 and Takara and Harrell (14.3%). 10 These numbers were much lower than the incidence of musculoskeletal injury in New Zealand herding dogs 17,18 and UK service dogs, 14 likely because our population of dogs was quite young overall and the study period was relatively short. Additionally, our study showed there were multiple dogs that sustained more than 1 injury or illness during the period observed; however, we did not conduct further analysis on these multiple injuries.…”
Section: Discussionmentioning
confidence: 91%
“…A comprehensive prospective study 17 of 641 herding dogs in New Zealand showed that 43% had at least 1 musculoskeletal injury. In a subsequent study 18 of 323 dogs, 57% (n = 184) developed at least 1 musculoskeletal abnormality, and of these dogs available for follow-up, 68% developed a second musculoskeletal abnormality. Our study intended to determine the calculates the mean WSP for that injury type for the 24-month period (ie, a dog that had an acute musculoskeletal injury would be expected to have a 24-month WSP of 98.4% [vs 81.4% if the injury were chronic]).…”
Section: Discussionmentioning
confidence: 99%
“…Working farm dogs (such as sheep dogs) conduct important work including herding and guarding livestock ( 27 ), as well as providing companionship to shepherds working in isolated conditions ( 28 ). Where farm dogs work frequently, they may be susceptible to health issues; a longitudinal study conducted in New Zealand revealed that 60% of working farm dogs developed at least one musculoskeletal abnormality (any physical sign regardless of severity) over 4 years ( 29 ). Health complications can greatly affect a working dog’s quality of life, through pain and limited mobility, and may also place an economic burden on farmers.…”
Section: Introductionmentioning
confidence: 99%